2016
DOI: 10.3892/mco.2016.897
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted whole-body imaging with background body signal suppression/T2-weighted image fusion of gastrointestinal cancers

Abstract: Abstract. Diffusion-weighted whole-body imaging with background body signal suppression (DWIBS) yields positive results for cancer against the surrounding tissues. The combination of DWIBS and T2-weighted images (DWIBS/T2) in the diagnosis of gastrointestinal tract cancers was retrospectively analyzed in the present study. Patients were subjected to magnetic resonance imaging after cancer was diagnosed through specimens obtained via biopsy or endoscopic mucosal resection. Sixteen patients were assessed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…A major issue with adenomyomatosis of the gallbladder is differentiating it from gallbladder cancer (27). Our previous study has already reported that IPMN was negative on DWBIBS/T2 (28). The present study confirmed these negative results with PET/CT imaging.…”
Section: Discussionsupporting
confidence: 78%
“…A major issue with adenomyomatosis of the gallbladder is differentiating it from gallbladder cancer (27). Our previous study has already reported that IPMN was negative on DWBIBS/T2 (28). The present study confirmed these negative results with PET/CT imaging.…”
Section: Discussionsupporting
confidence: 78%
“…After removing 39 duplicates, we reviewed 131 titles and abstracts and excluded 118 studies for the following reasons: nonhuman studies (n = 3), case reports/letters/editorials/conference abstracts (n = 54), review articles/guidelines/consensus statements (n = 29), and studies outside the field of interest (n = 32). After reviewing the full text of 13 eligible articles, we excluded four for the following reasons: studies outside the field of interest (n = 3) and those with overlapping study populations (n = 2) . Ultimately, eight studies evaluating the diagnostic performance of DWI for GB lesions, including 557 patients, were included.…”
Section: Resultsmentioning
confidence: 99%
“…Images obtained from DWIBS are fused with their corresponding T2-weighted images using a workstation (13)(14)(15). DWIBS and T2-weighted image fusion (DWIBS/T2) enables anatomical evaluation of the positive signals obtained from DWIBS (16). Therefore, the present study retrospectively analyzed images obtained by DWIBS/T2 from patients with acute cholecystitis to determine how useful this technique is in the management of the disease.…”
Section: Introductionmentioning
confidence: 99%